Analysis Of The Influence Of Delivery Service Quality On Customer Satisfaction JNE Trucking Sub Agent Klaten - Ekowati, Maria Atik Sunarti; Rumekso, Ayub Widhi (iora, 2023)
The purpose of this study is to analyze the effect of the quality of freight forwarding services on customer satisfaction by using five variables, namely Tangible, Reliability, Responsiveness, Assurance, Empathy, and the variable customer satisfaction as a dependent variable. The population is all JNE customers, sampling on 30 respondents, using non-probability sampling technique and accidental sampling approach, anyone who is met can sample. The method used is descriptive statistics, multiple linear regression, validity and reliability test, T test, F test and the determinant coefficient (R2). The results of the analysis, research indicators are valid and reliable, does not happen heteroscedasticity seta normally distributed.